Pengaruh Pemberian Kombinasi Zat Pengatur Tumbuh Terhadap Pembentukan Tunas Bunga Lili (Lilium longiflorum THUNB) Secara in vitro - Berlian Zetikarya Haryati (LPPM UKI Toraja, 2017)
The research aimed to know the effect of combination supplement plant growth regulator cytokinin BA with auksin NAA or 2,4-D to bud formation of lili flower (Lilium longiflorum Thunb) in vitro. Research had been conducted in the tissue culture laboratory of University State Manado in Tondano. The research used factorial completely randomized (CRD) consist of two experiments i.e cytokinin BA (B) auksin NAA (N); 2,4-D (D) with three replications and consist of ninety six treatment units. The observartion demand after ten month initiation. The results of the study showed that there was a very significant different of interaction auksin NAA and cytokinin BA of bud formation lili (Lilium longiflorum Thunb) in vitro. The medium was found positif performance for inducting callus on B2N4 ( 0,25 mg/L BA + 1,5 mg/L NAA). The treatment B4N4 ( 0,75 mg/L BA + 1,5 mg/L NAA) and B3N4 ( 0,5 mg/L BA + 1,5 mg/L NAA) producted bud and callus. Interaction auksin NAA and 2,4-D and cytokinin BA producted bud on B3D3 ( 0,25 mg/L BA + 2 mg/L 2,4-D), B3D2 ( 0,25 mg/L BA + 2 mg/L 2,4-D) and B4D2 ( 0,75 mg/L BA + 1 mg/L 2,4-D) treatment.